Primary gynecologic lymphoma when diagnosed by a gynecologist: A case series - Alexandra J. Lamacki; Caroline Montag; Elizabeth Kertowidjojo; S. Diane Yamada; Katherine C. Kurnit (Elsevier, 2024)
Introduction: Primary lymphomas of the gynecologic tract are a rare pathology that may present with typical gynecologic symptoms. Unlike other gynecologic malignancies, surgical management is not considered an essential part of the treatment regimen for gynecologic lymphomas but may be required for diagnosis. The purpose of this series is to report on symptom presentation and management from the gynecologic specialist's perspective. Methods: Records from an institutional pathology database identified patients diagnosed with primary gynecologic lymphoma between 1993 and 2023. Results: Eight patients were identified for this series. Patients presented with pelvic pain, abnormal vaginal bleeding, and/or a mass on pelvic exam. The majority were diagnosed with lymphoma only after surgical resection. The most common pathology was diffuse large B-cell lymphoma (DLBCL). Seven of the eight patients received chemotherapy, which was administered by a medical oncologist. Conclusions: Our series highlights the presentation, diagnostic workup, and management of gynecologic lymphomas with attention to the role of surgical management and intraoperative pathologic evaluation as well as medical treatment of these cancers after surgical debulking.